ATP5D Is a Potential Biomarker for Male Fertility. (11th January 2023) - Wang, Yi-Bo; Zhai, Chen-Yang; Yao, Guan-Ping; Chen, Ting-Bao; Xue, Lu-Lu; Zhou, Lin; Xiong, Liu-Lin; Wang, Ting-Hua
Abstract : Background. Infertility is a global medical and social problem that affects human health and social development. At present, about 15% of couples of the right age in the world are infertile. As all we know, genetic defects are the most likely underlying cause of the pathology. ATP5D is also known as the delta subunit of mitochondrial ATP synthase. Mitochondria maintain sperm vitality, capacitation, acrosome reaction, and DNA integrity through ATP. Mitochondrial damage can trigger energy synthesis disorders, resulting in decreased sperm quality and function or even disappearance. The specific role of ATP5D in regulation of the male reproductive system remains elusive. Methods. In this study, semen from normal and infertile males were collected and their indicators were examined by analysis of routine sperm parameters; ATP5D protein content in semen was examined by ELISA. Singer sequencing was used to detect whether there was a mutated of ATP5D in semen. Meanwhile, ATP5D knockout (KO) and knockin (KI) male mice were selected at 8-12 weeks of age and mated with adult wild-type (WT) female mice for more than two months to assess their fertility and reproductive ability. Morphological changes in tissues such as testes and epididymis were observed by HE staining; spermatozoa were taken from the epididymis of the mice; sperm counts were performed and morphological changes were observed by Diff-Quik staining. Results. The results showed that the expression of ATP5D in infertile males was significantly lower than that in normal males (P < 0.001 ) and the normal morphology rate of spermatozoa was much lower than that of normal males, and the sequencing results showed no mutations. The animal reproductive experiments showed no significant changes in the number of fertility in KO/KI mice compared with WT mice, but the duration of fertility was significantly longer (P = 0.02 ). The testicular cells in KO mice were loosely arranged and disorganized, the lumen was larger, the interstitial cells were atrophied, and the number of spermatozoa was reduced and the malformation rate was higher in WT males. This suggests that ATP5D is an essential protein for sperm formation and fertility in male mice and may be used as a biomarker of male fertility. Conclusion. This study found ATP5D correlated with male infertility and the expression levels were significantly reduced in the seminal plasma of all male infertile patients without gene mutations. KO male significantly prolonged fertility time and impaired testicular histomorphology. This suggests that ATP5D may be associated with spermatogenic function and fertility in male mice and may be used as a biomarker for male fertility. Future studies are required to elucidate the potential mechanisms. The trial registration number is KLL-2021-266.